Extraction of Bioactive Compounds from Coffee Husk with Acetone Using Microwave Assisted Extraction Method and Analysis of Phenolic Compounds - Theressa Julieta Putri Andina; Helda Wika Amini; Ansori Ansori; Yukti Nurani; Ratri Sekaringgalih; Sonya Hakim Raharjo; Merymistika Yufrani Afred (JOBC, 2024)
. Nowadays, coffee husks are limited to animal feed and fertilizer. Therefore, a study used Robusta coffee husk waste as a raw material. The purpose of this study was to determine the effect of several variables and to determine the optimum conditions in the process of extracting bioactive compounds from coffee husk waste. The coffee husk contains bioactive compounds, including anthocyanins and polyphenol compounds, such as flavonols, flavan-3-ols, hydroxycinnamic acids, and caffeine. Coffee husk waste will be extracted using the Microwave-Assisted Extraction (MAE) method with acetone solvent, with several variables: the ratio of material to solvent, microwave power, and extraction time. Analysis of the identification of phenolic compound content was then also carried out using UV-Vis spectrophotometry. The variables of material ratio, extraction time, and microwave power were proven to be interrelated so that they could produce total phenol at optimum conditions. The optimum conditions for extracting bioactive compounds from coffee husk waste were obtained at a material ratio of 0.04 g/mL, 9 minutes, and power of 300 watts, with a total phenol yield of 8.65 GAE/g sample.